Brazilian Test On Mechanical Behaviors Of Anisotropic Rocks - Khadri, Nurmaliana Mohd (Universiti Sains Malaysia, 2017)
Anisotropic rocks are the properties of rock which vary with direction. This property may affect tunnelling, quarrying operation and also petroleum engineering in controlling borehole deviation, stability and deformation. The samples are taking at two different sites in Perak which is LafargeHolcim at Kanthan and Hume Cement at Gopeng. The sample at these two sites maybe same in properties as there are the limestone. However, it may also be different at some aspect since it is occurred at the different places.The experimental study in this project focused on the failure strength and fracture pattern of anisotropic rocks under Brazilian test. , At the end of this experiment, failure strength is expectedly correlated with relative layer orientation. The failure strength is also expectedly correlated with relative layer activation fracture length for the tested sample. The higher the inclination angle the lower the failure strength. The highest tensile strength occurred at 0⁰ which is 16.77 MPa and the lowest occurred at 75⁰ which are 5.68 MPa for LafargeHolcim. For the Hume cement, the highest tensile strength occurred at 0⁰ which is 13.23 MPa and the lowest occurred at 90⁰ which are 6.42 MPa for Hume Cement.